Application of kinesiotherapy and electrothermotherapy in the treatment of elderly with knee osteoarthrosis: a comparative study - Fabiano de Jesus Furtado Almeida; Ana Eugênia Ribeiro de Araújo e Araújo; Carolina Abreu de Carvalho; Poliana Cristina de Almeida Fonsêca; Vinícius José da Silva Nina; Elba Gomide Mochel
Abstract Introduction Among the treatment modalities in this disease , the surgical and conservative means stand out through therapy resources such as electro-thermotherapy and kinetic therapy. The general objective of this study was to evaluate the effects from two protocols of physical therapy in elder women with knee osteoarthritis. Methods An experimental clinical trial type study consisting of pre and post tests was performed, in which 30 female patients were selected, all between 61 and 80 years old, diagnosed with primary knee OA, treated at the Center for Comprehensive Health Care for the Elder (CAISI - Centro de Atenção Integral à Saúde do Idoso). They were divided into 2 groups of 15 persons for each type of treatment: Group I was treated with kinetic therapy, and group II was treated with electro-thermotherapy. Patients from both groups underwent 36 physical therapy sessions during 12 weeks. For data collection, protocol sheets with socio-demographic data, Body Mass Index (BMI) at kg/m2, visual analogue scale (VAS) and measurement of motion range (ADM) were used. For statistics analysis, the Mann-Whitney, Wilcoxon and Chi-square's non-parametric tests were used. Student's parametric tests were also applied as independent samples. Results The tests performed in both groups contributed to the reduction in the level of pain. There were differences in group I and II on the increase of ADM, except in bending the left knee in group II. Conclusion It was concluded that both treatment modalities showed effective therapeutic responses, but these benefits were even higher in OA treatment by kinetic therapy.